GAMBARAN FUNGSI INTELEKTUAL LANJUT USIA DI KELURAHAN MOTOBOI BESAR, KECAMATAN KOTAMOBAGU TIMUR - Tjomo, Vika; Kristamuliana; Rompas, Sefti S. J (JURNAL KEPERAWATAN, 2024)
Background: The elderly generally experience a decrease in functional capacity, one of which is a change in cognitive function, which results in a decrease in the intellectual function of the elderly. Of the 6 elderly people who were interviewed in Motoboi Besar Village, 5 forgot their date of birth and the "today" date they were asked about..Objective: of the study was to find out about the intellectual function of the elderly in Motoboi Besar Village, East Kotamobagu District..Methods:This type of research is quantitative and uses a descriptive design; the method in this study is the survey method. The sample taken was composed of 85 respondents. The instrument used is the SPMSQ questionnaire. The data analysis in this study is univariate. Results: it was found that the elderly in Motoboi Besar Village, East Kotamobagu, had the most intact intellectual functions, namely 53 (62.4%) respondents; intellectual functions that experienced mild damage were 16 (18.8%) elderly respondents; and intellectual functions that experienced moderate damage were 14 (16.5%) elderly respondents.Conclusion: In this study found that the elderly respondents in Motoboi Besar Village, East Kotamobagu, mostly have intact intellectual functions.For future researchers, further research is needed regarding cognitive function,such as the relationship of lifestyle and cognitive function elderly.   Keywords:  Elderly intellectual functions; Elderly